2017
DOI: 10.5144/0256-4947.2017.375
|View full text |Cite
|
Sign up to set email alerts
|

Drug shortages in large hospitals in Riyadh: a cross-sectional study

Abstract: BACKGROUNDDrug shortages are a serious and complex issue in any healthcare system. We conducted this study because the prevalence of drug shortages in Saudi Arabia is largely unknown, while there have been reports of shortages.OBJECTIVETo explore the prevalence and characteristics of drug shortages as well as identify strategies to minimize their impact on patient care and safety in large hospitals.DESIGNQuestionnaire-based cross-sectional study.SETTINGPharmacy departments in secondary and tertiary care hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 22 publications
(63 reference statements)
1
41
0
Order By: Relevance
“…A range of other clinical outcomes were also measured and reported in studies including drug-resistant mutations [49], use of inferior treatments [50, 51], rationing of medications [35, 52], quality of patient care [12, 13, 23], mechanical ventilation [48], and seizure frequency [22]. These can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of other clinical outcomes were also measured and reported in studies including drug-resistant mutations [49], use of inferior treatments [50, 51], rationing of medications [35, 52], quality of patient care [12, 13, 23], mechanical ventilation [48], and seizure frequency [22]. These can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, medication shortages have the potential to impact patient outcomes. The literature has reported that shortages have put economic burdens on the health system, interfered with patient care, and have led to patient dissatisfaction [12, 13]. Medication shortages have also been reported to increase patient out of pocket costs [13, 14] and most alarmingly they have led to adverse patient events including mortality, treatment changes, inferior treatment, and medication errors [13, 15].…”
Section: Introductionmentioning
confidence: 99%
“…An exploratory qualitative analysis using stakeholder discussion for data generation was conducted. The discussion points were generated after conducting extensive literature review of similar studies (Fox et al, 2014, Reis and Perini, 2008, Gray and Manasse, 2012, Pauwels et al, 2014, Balkhi et al, 2013, Pauwels et al, 2015, Alsheikh et al, 2016, Setayesh and Mackey, 2016, Alshehri and Alshammari, 2016, AlRuthia et al, 2017, Food and Drug Administration Safety and Innovation Act, USC, 2012, Iqbal et al, 2017, Haaijer and Joncheere, 2003, WHO, 1988, MSH, 2009, WHO, 2017, APICS, 2014, Rasooldeen, 2017, Barlas, 2013, Yang et al, 2016). The topics included to guide the discussion were: current situation of drug shortages in Saudi Arabia, major factors contributing to drug shortages, challenges and obstacles to improve drug supply, and stakeholders’ recommendations for managing drug shortages.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the prevalence and causes of drug shortages in different countries and health care institutions (Pauwels et al, 2014, Balkhi et al, 2013, Pauwels et al, 2015, Alsheikh et al, 2016, Setayesh and Mackey, 2016). Although a few studies have investigated drug shortages in Saudi Arabia, most of these studies were based on questionnaires administered to hospital pharmacists to explore the prevalence of drug shortages and how their institutions are coping with them (Alshehri and Alshammari, 2016, AlRuthia et al, 2017). Nevertheless, the root causes of drug shortages in Saudi Arabia have not been fully investigated before mainly due to the unavailability of published data.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, drug shortages have been frequently reported over the past five years due to a multitude of reasons [ 10 , 11 , 12 , 13 ]. However, this pandemic has exacerbated the situation both locally and globally [ 14 ].…”
Section: Introductionmentioning
confidence: 99%